VARIASI MORFOLOGI DAN ANATOMI Sargassum spp. DI PANTAI BAYAH BANTEN - - Triastinurmiatiningsih; - Ismanto; - Ertina (Universitas Pakuan, 2011)
Sargassum is one of the genus including in Class Phaeophyceae. Sargassum spp. are found as many as 150 species in zone waters tropic, subtropic and frigid zone. This research to know variation morphology and anatomy Sargassum spp. which found in Bayah Beach. Result of the research will giving knowledge for different Sargassum species based on variation morphology and anatomy. Research methods divided of three work phases that are collect in the field, morphology observation and anatomy observation. Collect alga in the field with execute transek method, morphology observation with differents variation formed from cauloid, branching type, filoid, cryptostomata, midrib (middle vein filoid), vesicle (float) dan receptacle (reproduction organ). Anatomy observation with measure length and wide cells, analize cells shape, counting cells amount (enlargement 160 x), from each parts cortex and medulla by cauloid and filoid Sargassum spp. Based observation results are found 7 species Sargassum that are Sargassum binderi, S. cinereum, S. echinocarpum, S. duplicatum, S. plagyophyllum, S. crassifolium dan Sargassum sp. which have in Bayah Beach, South Banten. Such a thing resulted is show that have morphology variation supported by anatomy variation.Â Key word : Sargassum, morphology and anatomy, Bayah